Stimuli-responsive metal–organic framework hydrogels endow long carbon fiber reinforced polyetheretherketone with enhanced anti-inflammatory and angiogenesis and osteogenesis. (January 2023) - Dong, Wenying; Zhao, Shanshan; Wang, Yilong; Zhou, Xingyu; Jiang, Junhui; Dang, Junbo; Sun, Dahui; Dai, Xin; Zhang, Mei; Jiang, Zhenhua
Graphical abstract: Highlights: LCFRPEEK with a MOF hydrogel surface is prepared for enhancing anti-inflammatory and angiogenesis and osteogenesis. The MOF hydrogel is composed of HAP@Mg-GA MOF nanoparticles with core–shell structure and pH-sensitive methacryloyl chitosan. This implant has excellent pH-sensitive biomolecule release capabilities. The multifunctional implant displays excellent anti-inflammatory and angiogenesis and osteogenesis in vitro and in vivo. Abstract: The ideal orthopedic implant has sufficient biomechanical strength and physiological activity to coordinate with the intricate physiological healing process of the tissue. Herein, multifunctional stimuli-responsive metal–organic framework (MOF) hydrogels on the surface of the sulfonated long carbon fiber reinforced polyetheretherketone (LCFRPEEK) implant using the UV-grafting method is constructed to coordinate with the osseointegration process. The hydrogels are composed of nano-hydroxyapatite cored magnesium-gallic acid (HAP@Mg-GA) MOF nanoparticles and methacryloyl chitosan. The stimuli-responsive MOF hydrogels exhibit outstanding pH-sensitive biomolecule release capabilities. The outcomes of in vitro cell experiments demonstrate that the multifunctional sulfonated LCFRPEEK could actively and precisely perform immunomodulation, timely scavenge excess ROS and reduce NO production under the immune environment (low pH), as well as promote angiogenesis and osteogenic differentiation benefiting from the cooperation of GA, Mg 2+ and Ca 2+ . Furthermore, the in vivo SD rat subcutaneous implantation and rabbit tibia defect models further demonstrate that the implant has superior in vivo immunomodulation, angiogenesis, osteogenic differentiation, and osseointegration abilities. Therefore, the study provides a new multifunctional orthopedic implant that can achieve osseointegration, which broadens the effective application of LCFRPEEK biomaterials in orthopedics.